Work with administrators to create a concealed‐carry policy. Issue 3 (21st June 2018) - Hope, Joan
Abstract : DALLAS — Concealed carry on campus: It's a hotly contested topic both at colleges and universities and in state legislatures. If your institution doesn't have a policy in place, or needs to revise its policy based on changes in state law, you're likely to be involved in discussions about the policy and how to word it.